Weekly paclitaxel in patients with recurrent or persistent advanced ovarian cancer. Issue 2 (1st February 2003) - Ghamande, S.; Lele, S.; Marchetti, D.; Baker, T.; Odunsi, K.
Abstract : The purpose of the study is to assess the role of palliative chemotherapy with weekly paclitaxel in patients with persistent or recurrent advanced ovarian cancer. Twenty-eight patients with predominantly paclitaxel- and platinum-resistant ovarian cancer disease were treated with weekly paclitaxel at 80 mg/m 2 for 6–8 weeks. In 25 patients (89.2%), this combination represented at least a third line of therapy and for 14 patients (50%) it was more than the fifth line. A clinical response rate of 50% (14 partial responses) was obtained in the 28 patients with evaluable disease. Five patients (17.9%) had stable disease and nine patients (32.1%) had progression of disease. In patients with stable disease or a response, the median progression-free interval was 6 months and overall median survival is 8+ months. All the responses in paclitaxel-resistant tumors were seen in patients with a paclitaxel-free interval of more than 12 months. This regimen is well tolerated with acceptable toxicity. These data suggest that weekly paclitaxel has considerable antitumor activity in heavily pretreated patients with platinum- and paclitaxel-resistant advanced ovarian cancer.